Triaxial behavior and microstructural insights of loose sandy soil stabilized with alkali activated slag - Mohammad Banaian; Seyed Mohammad Fattahi; Abbas Soroush; Alireza Komaei (Scientific Reports)
Abstract This study investigates the mechanical and microstructural properties of loose sandy soil stabilized with alkali-activated Ground Granulated Blast Furnace Slag (GGBFS). To examine the effects of varying GGBFS contents, curing times, and confining pressures on mechanical behavior, undrained triaxial and unconfined compressive strength (UCS) tests were conducted. Microstructural analyses using FE-SEM, EDX, and FTIR were performed to elucidate the nature and development of cementation. The results of mechanical behavior demonstrate that even with limited GGBFS content (1–6%), the treated samples exhibited significant improvements in strength, stiffness, and energy absorption, underscoring the efficiency of alkali-activated GGBFS as a soil stabilizer. Moreover, mechanical parameters from triaxial tests revealed a nearly constant internal friction angle with increasing GGBFS content and curing duration, while cohesion showed remarkable enhancement. A strong linear correlation between UCS and cohesion was also identified, enabling cost-effective estimation of shear strength parameters. These findings highlight the potential of alkali-activated GGBFS for improving granular soils, offering practical implications for sustainable geotechnical applications, particularly in road construction.